2012
DOI: 10.7439/ijbr.v2i12.204
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Foetal Outcome in Pregnancy Induced Hypertension: A Study From Rural Tertiary Care Teaching Hospital in India

Abstract: Background: Preeclampsia and eclampsia have been recognized as clinical entities since the times of Hippocrates. Pregnancy induced hypertension (PIH) is one of the commonest disorders associated with the increased risk of maternal and fetal complications. It is reported in the world literature that the incidence of eclampsia is on the decline, but still a menace in developing countries. Objectives: To study the maternal and foetal outcome in pregnancy induced hypertension. Material and Methods: A prospective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 9 publications
10
39
1
Order By: Relevance
“…which is comparable but less than the incidence in the studies done by Chhabra S et al 5.2% and Sundaram S 5% and by Bangal V et al 7.26%. [3][4][5] In the present study, the incidence of eclampsia was 0.9% which is more or less the same showing a marginally decreasing trend compared to studies done over the past 10 years. This may be attributed to increased awareness, early diagnosis and prompt treatment of pre eclampsia.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…which is comparable but less than the incidence in the studies done by Chhabra S et al 5.2% and Sundaram S 5% and by Bangal V et al 7.26%. [3][4][5] In the present study, the incidence of eclampsia was 0.9% which is more or less the same showing a marginally decreasing trend compared to studies done over the past 10 years. This may be attributed to increased awareness, early diagnosis and prompt treatment of pre eclampsia.…”
Section: Discussionsupporting
confidence: 55%
“…In this present study number of vaginal deliveries 117 (50%) were equal to the number of caesarean deliveries 117 (50%) which is similar to the study done by Uddin AW et al 7 In which the rate of cesarean section is about 50.8% where as in the studies done by Bangal V et al and by Parmar MT et al is 35% and 37% respectively (Table 7). 5,6 This comparatively higher rate of caesarean section in our study is attributed to the fact that our institution is a tertiary referral centre situated in the rural area and most of the patients were referred after development of complications. HELLP syndrome is characterized by hemolysis, elevated liver enzymes and low platelet counts.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Fox noted that in many hypertensive gestations there is decreased foeto-placental weight ratio because of a compensatory hypertrophy of placenta under the influence of cases of mild, severe PIH and eclampsia respectively. Kapoor et al concluded that, the incidence of premature babies was 23% in PIH and prematurity was one of the major risk factors for increasing the perinatal mortality [29]. [30].…”
Section: Observations and Resultsmentioning
confidence: 99%
“…33 Bangal et al excluded gestational HTN and clubbed mild and severe PIH. 34 While Mohammed et al have studied the variations of platelet indices in PIH in a fixed study group of 20 cases each under each category, whereby the incidence of each cannot be commented upon and Parmar et al have categorized PIH cases into mild, moderate and severe PIH. 35,36 Wolde et al's method to categorize cases with PIH based on the National High BP Education Working Group (2000) criteria has been done in this study owing to feasibility and simplicity of categorization into the five mentioned groups.…”
Section: Discussionmentioning
confidence: 99%